Improving the quality of neonatal care in Nigeria through the education of maternity health workers. Issue 3 (June 2021) - Emmanuel, Andy; Kain, Victoria J.; Forster, Elizabeth
Abstract: This study was undertaken to determine the impact of an educational intervention on health care workers' level of satisfaction with the training and the new knowledge gained regarding newborn care. A pre- and post-training knowledge survey, a 'satisfaction' survey and group discussions were conducted with 38 health workers at Jos University Teaching Hospital (JUTH), Plateau state, Nigeria. The content included in the training were rated as either 'very good' or 'excellent' by the majority (94.6%) of the participants. The majority (83.7%) strongly agreed that they would be able to apply most of the material learned to their job. And lastly, the mean post-training score (21.42 ± 1.08) was higher that the pre-training score (17.95 ± 3.08). The newborn care training resulted in a positive experience for the participants and improved their knowledge about newborn care. This study has potentially laid a foundation for positive behaviour change and improved neonatal care and survival in Nigeria.